Adsorption of ferrous ions onto phosphoric acid-activated biochar - Gabrielle Schultz Braz; Jaqueline do Carmo Lima Carvalho; Josiane Gonçalves de Andrade; Antônio Teodoro Dutra Junior; Robson Pereira de Lima; Evaneide Nascimento Lima; Osania Emerenciano Ferreira; Magno André de Oliveira; Augusto César da Silva Bezerra; Alan Rodrigues Teixeira Machado (Desalination and Water Treatment)
This study investigated the adsorption capacity of ferrous ions (Fe2+) using biochar derived from sugarcane bagasse, activated with phosphoric acid, and subjected to thermal treatment at temperatures ranging from 300 °C to 1000 °C. The objective of this study was to optimize the conditions for maximizing biochar adsorption efficiency. Comprehensive characterization was performed via thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). The FTIR spectra revealed the formation of aromatic structures, whereas the SEM analysis demonstrated increased porosity and uniformity in the samples treated at higher temperatures. The highest adsorption capacity for Fe²⁺ was 55.55 mg/g for the biochar sample treated at 1000 °C (B-1000P), which also had a surface area of 246.85 m²/g. Adsorption kinetics followed the pseudo-second-order model, indicating that chemisorption was the predominant adsorption mechanism. These findings underscore the potential of activated biochar for efficient wastewater treatment, offering a sustainable and effective approach to removing Fe2+ from contaminated water sources.